DISCOURSE ANALYSIS OF NARRATIVE VOICE IN NOVELS - Shokirova Marhabo Sharifovna,; Sobirova Umidaxon A’zamjon qizi, (TADQIQOTLAR, 2025)
Abstract. This article examines the concept of narrative voice in novels from a discourse-analytical  perspective.  Narrative  voice  is  understood  as  a  linguistic  and discursive  construct  that  shapes  how  stories  are  told  and  interpreted.  Drawing  on theories  of  discourse  analysis,  narratology,  and  stylistics,  the  study  explores  how grammatical  choices,  deixis,  modality,  and  speech  representation  contribute  to  the construction  of  narrative  voice.  Through  qualitative  textual  analysis,  the  article demonstrates that narrative voice plays a crucial role in mediating meaning, ideology, and reader engagement in fictional discourse.